Synthesis and deposition of ultrafine noble metallic nanoparticles on amino-functionalized halloysite nanotubes and their catalytic application. (January 2015) - Zou, Meiling; Du, Mingliang; Zhang, Ming; Yang, Tingting; Zhu, Han; Wang, Pan; Bao, Shiyong
Graphical abstract: Ultrafine noble metal nanoparticles are synthesized on N-HNTs using EGCG as both a green reductant and stabilizer and the nanocomposites show amazing reduction activity and recycle stability toward to 4-NP. Highlights: Ultrafine noble metal nanoparticles are synthesized on N-HNTs. EGCG was applied as both a green reductant and stabilizer to the metal NPs. The nanocomposites showed amazing reduction activity and recycle stability toward to 4-NP. Abstract: Using epigallocatechin gallate (EGCG) as both a green reductant and stabilizer, ultrafine noble metal nanoparticles (Rh NPs, Pt NPs, Pd NPs) are synthesized and in situ deposited within amino-functionalized halloysite nanotubes (N-HNTs) via a facile and eco-friendly process. These noble metal nanoparticles with extremely small size (∼1.5 nm) are dispersed densely and uniformly on both outside and inside surface of N-HNTs. Rh deposited N-HNTs (Rh–N-HNTs) was investigated as a model composite catalyst and applied in the catalytic reduction of 4-nitrophenol (4-NP), and it exhibited amazing activity and recycle stability. Due to the green and flexibility of the technique described here, noble metal nanoparticles, metal nanoalloy, or metal oxide nanoparticles with ultrafine particle size also can be loaded densely and uniformly on the surface of diverse amino-functionalized nanotubes, nanofibers or nanoporous, and these composites may be applicable in catalysis, photocatalysis, and electrochemical areas.